Investigation of the Propagation Characteristics of Underwater Shock Waves in Underwater Drilling Blasting. (15th January 2018) - Liu, Xin; Gu, Wenbin; Liu, Jianqing; Wang, Zhenxiong; Xu, Jinglin; Cao, Tao
Abstract : During the first-stage project of the main channel of Ningbo-Zhoushan Port's Shipu Harbor, underwater shock waves were monitored. By analyzing a typical measured pressure time history curve, the characteristics of underwater shock waves in an engineering context were obtained. We obtained a traditional exponential attenuation formula for underwater shock waves based on the measured data, simplified the model of underwater drilling blasting based on engineering practice, deduced a revised formula for underwater shock wave peak overpressure on the basis of dimensional analysis, established a linear fitting model, and obtained the undetermined coefficients of the revised formula using a linear regression analysis. In addition, the accuracies of the two formulas used to predict underwater shock wave peak overpressure and the significance order of influence and influence mechanism of factors included in the revised formula on the underwater shock wave peak overpressure were discussed.